Prevalence of mesiobuccal-2 canals in maxillary first and second molars among the Bruneian population-CBCT analysis - Hui Yi Onn; Malissa Siao Yun Abdullah Sikun; Hanif Abdul Rahman; Jagjit Singh Dhaliwal (Nature Publishing Group, 2022)
Abstract Introduction Identification of the second mesiobuccal canal (MB-2) in maxillary molars is considered an endodontic concern of many practitioners due to its complex morphology. The use of Cone-beam Computed Tomography (CBCT) is a necessity for easier location of this elusive canal during endodontic treatment. Aim To study the prevalence of the MB-2 canal in the maxillary first and second molars amongst the Bruneian population. Materials and methods A retrospective study involving a review of scans taken from a CBCT scanner (J Morita; Veraviewepocs 3D R100 Panoramic/Cephalometric) over a 5-year period, from May 2016 to May 2021 was carried out. A total of 342 maxillary molars were evaluated independently by two observers. Any contradicting outcomes were discussed by both observers until a consensus was reached. In addition, the correlation of MB-2 canals with gender and age were calculated using the chi-squared test. Results The prevalence of MB-2 canal in the maxillary first and second molars are 51.3% and 29.8% respectively. Both males and females have a similar prevalence of MB-2 canals in the maxillary first and second molars. The incidence of MB-2 canals in both maxillary first and second molars significantly decreases with increasing age. No significant correlation between the prevalence of MB-2 canals with different gender groups in the population. Conclusions It is crucial for clinicians to identify the presence of MB-2 canals when performing endodontic treatment of the maxillary first and second molars. Varying prevalence has been reported for different populations. Recognising this wide-ranging prevalence amongst different populations will allow for greater predictability in ensuring endodontic treatment success.